The sensory perception as “experiencing-as” in John Hick’s philosophy of religion – selected issues - Strzyżyński, Przemysław (Filozofia Chrześcijańska, 2024)
In the article I present the role of the concept of sensory cognition in John Hick’s philosophy of religion. I present Hick’s argument for the similarity of religious beliefs to scientifi c knowledge. Hick does this by introducing an element of interpretation in each of the four areas of knowledge: sensual, aesthetic, moral and religious. Then I present how, based on sensory knowledge, Hick tries to demonstrate the rationality of religious beliefs. We are talking here about rational religious belief without proofs. Finally, I show how, based on the concept of sensory cognition, Hick proposes the so-called the hypothesis of religious pluralism.